(untitled) (Balthazar, 2021)
For numerous women poets of the 20th century, the concept of identity and the concept of boundary are often two parts of the same discourse. This paper/article examines how some women writers have used words, either in prose or poetry, as a tool to construct or reconstruct identities so as to make order out of their past, albeit arbitrarily at times, and thus make it tolerable. For some of them, the reconstruction of one’s life, that is salvation as achieved through writing, requires the shifting of many boundaries—social, psychological, geographical, etc. Such is the point of view here used to look at the writings of Agota Kristof, Janet Frame, Mariella Mehr, Jozefina Dautbegović, Dalia Rabikovitch.